Upaya Pustakawan dalam Meningkatkan Literasi Peserta Didik SMA Negeri 1 Karangreja - Marti; Laugu, Nurdin (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
In the current era of globalization, increasing literacy in libraries is important, affecting the efficiency of services to users. This research aims to explain librarians' efforts to increase literacy at SMA Negeri 1 Karangreja. Descriptive qualitative methods are used to describe these efforts. The research results show effective strategies, such as a weekly literacy schedule, age-appropriate book selection, and incentives for active readers. Improving literacy also includes fun reading activities, creativity space, access to reading materials, use of technology, and collaboration with the journalist community and internet access. The role of librarians is key in providing satisfactory services to users, through good communication and dedicated service in the library.